Analisis Konstruksi Makna Kata Khasyyah Perspektif Al-Qur’an: (Sebuah Tinjauan Semantik Ensiklopedik) - Muhamad Khabib Imdad Muhamad Khabib Imdad (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2025)
The language of the Qur’an possesses a distinctive aesthetic through the lexical filtration of each fragment, wherein specific meanings and purposes are embedded and must be explored comprehensively. This study positions itself within that tradition by examining one of the frequently recurring terms in the Qur’an, khasyyah. This word is often interpreted as "fear," yet it carries various characteristics and nuanced connotations. The present article seeks to provide an essential exposition on the semantic depth of khasyyah in the Qur’an, including its categorization when directed toward Allah, thereby offering a broader discourse on the conceptual richness of the term. Methodologically, this study adopts a qualitative paradigm by applying the principles of library research. The secondary sources are drawn primarily from the anatomy of the Qur’an, focusing solely on the analysis of khasyyah and its derivations. This data is further supported by relevant references such as classical Arabic dictionaries, Qur’anic exegesis, scholarly books, and academic articles. For the analytical framework, the study employs the encyclopedic semantic method, which aims to trace the semantic trajectory of khasyyah within the Qur’anic discourse. The findings reveal that this term appears in multiple derivative forms throughout the Qur’an, producing a range of meanings. These include the classification of khasyyah as both a stimulative and resultant emotional response toward Allah, as well as other correlational meanings such as hardship (masyaqqah), compulsion, anxiety, calamity, despair, and war.